Evaluation of the Resource Potential of High-Carbon Rocks of the Saraylin Series Within the Southeastern Slope of North Tatar Arch in the Republic of Tatarstan - A. F. Safarov; R. R. Aflyatunov; A. A. Lutfullin; A. M. Kalimulli; R. M. Khabipov; K. D. Shumatbaev; V. G. Bazarevskaya; S. A. Vakhromeev; E. N. Poludetkina; A. G. Kalmykov (Georesursy, 2025)
The paper presents results of comprehensive study of core samples collected from Tournaisian sediments of the Saraylin Series within the Nizhnekamsk Uncompensated Trough. The survey region covers the southeastern slope of North Tatar Arch in the Republic of Tatarstan. The study is targeted at the Saraylin Series, a complex of carbonatesiliceous-terrigenous rocks with increased organic matter content, confined to the interval from the lower boundary of the Tournaisian Stage to the bottom of overlying Tournaisian carbonate rocks or terrigenous sediments of another (postTournaisian) age.Samples from two wells confined to axial and flank regions of the trough were investigated. For the first time ever, the Saraylin sediments of the Republic of Tatarstan were characterized by core data to enable identification of the main lithofacial and geochemical features.Results of pyrolysis studies of the entire coring interval were analyzed. Vertical and horizontal variations of pyrolytic parameters of the sediments within the section were established. Is has been established, that the Saraylin sediments in the axial and flank regions of the trough are high-carbon, predominantly domanicites and domanicoids. Organic matter is represented by type II kerogen and has low maturity at PK3-MK1 level.The resource potential of Saraylin sediments was evaluated within one paleofacial zone of axial region of the trough based on core data. Five lithologic and geochemical clusters were identified considering nonuniform distribution of organic matter content and other geochemical characteristics of the sediments through the section.Based on the resulting data, the resource potential of the rocks in the lower portion of the Saraylin Series was estimated. The amount of liquid hydrocarbons, mobile petroleum reserves and residual kerogen generation potential were estimated. Results of the present research efforts enable refinement of the resource potential of high-carbon Tournaisian rocks of the Saraylin Series and provide improved understanding of their oil and gas potential within the southeastern slope of North Tatar Arch.